Further development of spinal cord retreatment dose estimation: including radiotherapy with protons and light ions. (2nd December 2021) - Moore, Joshua W.; Woolley, Thomas E.; Hopewell, John W.; Jones, Bleddyn
Abstract: Purpose: A graphical user interface (GUI) was developed to aid in the assessment of changes in the radiation tolerance of spinal cord/similar central nervous system tissues with time between two individual treatment courses. Methods: The GUI allows any combination of photons, protons (or ions) to be used as the initial, or retreatment, radiotherapy courses. Allowances for clinical circumstances, of reduced tolerance, can also be made. The radiobiological model was published previously and has been incorporated with additional checks and safety features, to be as safe to use as possible. The proton option includes use of a fixed RBE of 1.1 (set as the default), or a variable RBE, the latter depending on the proton linear energy transfer (LET) for organs at risk. This second LET-based approach can also be used for ions, by changing the LET parameters. Results: GUI screenshots are used to show the input and output parameters for different clinical situations used in worked examples. The results from the GUI are in agreement with manual calculations, but the results are now rapidly available without tedious and error-prone manual computations. The software outputs provide a maximum dose limit boundary, which should not be exceeded. Clinicians may also choose to further lower the number of treatment fractions, whilst using the same dose per fraction (or conversely a lower dose per fraction but with the same number of fractions) in order to achieve the intended clinical benefit as safely as possible. Conclusions: The new GUI will allow scientific-based estimations of time related radiation tolerance changes in the spinal cord and similar central nervous tissues (optic chiasm, brainstem), which can be used to guide the choice of retreatment dose fractionation schedules, with either photons, protons or ions.